Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae) - Gilligan, Todd; Huemer, Peter; Wiesmair, Benjamin (Zootaxa, 2016)
Several species of Ancylis related to A. unguicella (Linnaeus) and A. geminana (Donovan) have been presumed by previous authors to be Holarctic. However, difficulty in identifying genitalic characters to define and separate these taxa has brought into question their true distribution and led to inconsistencies in their taxonomic treatment in Europe and North America. Here we use a combination of DNA barcode sequence data and morphology to resolve these taxonomic differences, determine the actual geographic range of these taxa, and describe three new species. In the A. unguicella group, only A. unguicella and A. uncella (Denis & Schiffermüller) are Holarctic in distribution. In the A. geminana group, none of the taxa are Holarctic in their distribution. Three species are described as new: A. christiandiana Huemer and Wiesmair, sp.n. (Austria, Germany); A. oregonensis Gilligan and Huemer, sp.n. (USA: Oregon); and A. saliana Gilligan and Huemer, sp.n. (USA: Florida). In addition, Ancylis carbonana Heinrich, syn.n., is synonymized with A. uncella; A. cuspidana (Treitschke), syn.rev., is synonymized with A. diminutana (Haworth); and A. diminuatana Kearfott, stat.rev., and A. subarcuana (Douglas), stat.rev., are raised from synonymy.